Patriotism Values in Toba Dreams Novel by TB Silalahi Analysis: Sociology of Literature - Ginting, Aga Fransiskho (Institute of Computer Science (IOCS), 2020)
Literary works are descriptions of human life experiences, which tell about family life and the process of achieving ideals that sometimes do not match what is desired. The purpose of this study is to find and interpret the patriotism values ??contained in the novel Toba Dreamskarya TB silalahi. The method used in this research is reading, listening, and taking notes. The data analysis technique is obtained from reading primary data, then interpreting existing data. Furthermore, describing the values ??of patriotism with the sociological approach of Endraswara literature. Based on the research findings of the novel Toba Dreamsini, it can be concluded that the values ??of patriotism can be divided into 5 forms, namely 1. Love the country. 2. Willing to sacrifice for the benefit of the nation and state. 3. Putting the unity, integrity and safety of the nation and state above personal and group interests. 4. Reformer spirit. 5. Never give up.